(untitled) (Journal of Hama University, 2021)
The aim of this research is to identify the factors affecting the market value of stocks by applying in the Islamic banks listed on the Damascus Stock Exchange, which consists of three banks (Syria International Islamic - Al-Baraka - Al-cham) during the period of time from 2015 until 2019, using the simple linear regression for a number of independent variables, namely: (return on equity, price book value , book value per share, earnings per share , turnover ratio , debt rate), and the results of the statistical analysis of each of Syria International Islamic and Bank Al- Barakah are the absence of a statistically significant effect between the market value of stocks and the following independent variables: (earnings per share, book value per share, debt ratio, turnover rate), and for Sham Bank it has been found that the factors that do not affect the market value of its stocks are (return on equity), On the other hand, the results of the study showed that the factors affecting the market value of stocks which have the ability to explain the changes in the value of stocks for the banks (Syria International Islamic and the Barakah ) are: (return on equity price book value), As for the cham Bank, the factors affecting the market value its stocks are: (earnings per share, debt ratio, price book value ).